Stabilization Of Mine Residues In Broken Hill, New South Wales - Leigh J. H (The Australasian Institute of Mining and Metallurgy, 1976)
A history is given of the dust control techniques developed and applied by the mining companies at Broken Hill. A history of the regeneration works undertaken since 1936 is out- lined. Particular emphasis is placed on the stabilization of mine residue dumps which are located throughout a belt of mining leases in the middle of the city and which began in 1937. The establishment of vegetation for dust control techniques is discussed in detail and a case study is given of the successful revegetation of the sides of a 650 metre long, 350 metre wide and 35 metre high residue dump.